Stiffness and flexural strength evaluation of cement stabilized PET blends with demolition wastes. (10th April 2020) - Arulrajah, Arul; Perera, Sahan; Wong, Yat Choy; Horpibulsuk, Suksun; Maghool, Farshid
Highlights: 3% cement stabilization of PET plastic blends with construction & demolition wastes. Evaluation of compressive strength and resilient modulus of cement stabilized blends. Resilient response, flexural modulus & fatigue life of cement stabilized blends. Strength & resilient parameters were reduced with blended PET percentage. Abstract: This study was conducted to assess the performance of cement stabilized polyethylene terephthalate (PET) blends with construction and demolition (C&D) waste, namely recycled concrete aggregate (RCA) and crushed brick (CB), as a pavement construction material. A suite of basic characterization tests was undertaken on 3% and 5% PET blends (by mass) with RCA and CB stabilized with 3% cement. The material strength evaluation of the PET blends were undertaken using unconfined compressive strength (UCS) test and the secant modulus results of the blends were also analyzed. Moreover, the resilient moduli (MR ) characteristics were evaluated by repeated load triaxial (RLT) test while the flexural strength and the fatigue life of the blends were evaluated by flexural beam tests. UCS results of the cement stabilized PET blends of RCA and CB satisfied the minimum requirement for 7 days of curing samples. Adding PET decreased the MR values of the C&D waste materials, whilst CB showed higher MR values than RCA. PET blends with CB showed high flexural modulus and fatigue life than PET blends with RCA. The cement-stabilized blends of 5% PET with RCA and CB were found to have physical and strength properties which comply with road authority requirements for pavement base/subbase construction.